Budgeting and budgetary control practices of Koforidua Polytechnic - Asamoah, Felix Oppong (2011)
A Dissertation Submitted To The Department Of Accounting And Finance, School Of Business, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration.